Korean street food in contemporary Indonesia: Glocalization in a semi-medium city - Mutahir, Arizal; Chusna, Aidatul; Rizkidarajat, Wiman; Taufiqurrohman, Muhammad; Makhasin, Luthfi (Jurnal Sosiologi Dialektika, 2024)
Korean street food in Indonesia is part of the ‘Korean Wave’ (hallyu) that hit Indonesia in the early 2010s. It is not difficult to find Korean street food in Indonesian cities. Korean street food has become part of urban culture in Indonesia. This research aims to analyze the existence of Korean street food in Indonesia using the concept of glocalization according to Roland Robertson. This research also analyze the glocalization of Korean street food in the local context in the form of halal Korean street food so that it is accepted and consumed by Indonesian people. This study uses a qualitative method with a case study approach as a research strategy. Data collection was carried out by means of observation, interviews, and documentation. The result of this study has shown that through various forms of glocalization, Korean street food has become part of Indonesian society. Korean street food has carried out relative syncretism of food through a process of particularization as universalization. This process is carried out by adopting the halal concept in Korean street food. The results of this research contribute to understanding the glocalization of street food in adopting the halal concept.